Seasonal Sediment and Nutrient Transport Patterns. Issue 4 (1st July 2014) - Moriasi, D. N.; Guzman, J. A.; Steiner, J. L.; Starks, P. J.; Garbrecht, J. D.
Abstract : It is essential to understand sediment and nutrient sources and their spatial and temporal patterns to design effective mitigation strategies. However, long‐term data sets to determine sediment and nutrient loadings are scarce and expensive to collect. The goal of this study was to determine seasonal patterns of suspended sediment (SS), total N (TN), and total P (TP) concentrations and loadings for three USGS gauge sites located at the Fort Cobb Reservoir Experimental watershed (FCREW) located in southwestern Oklahoma. Measured instantaneous discharge, SS, TN, and TP concentration data were used to develop lognormal water quality–discharge relationships. The water quality–discharge relationships were used to generate estimated seasonal concentrations and loads based on hourly or 30‐min interval discharge. The estimated concentrations and loads were used to determine seasonal patterns for SS, TN, and TP relative to the respective state water quality criteria. Decreasing and increasing monotonic trends were observed for the seasonal time series loads for all three sites, but they were insignificant based on the Spearman test (α = 0.05). The largest loads were estimated during the wet springs and summers. The study SS, TN, and TP target concentrations were exceeded in one season or another. The study results showed that the priority locations to implement the TN and TP conservation practices were the Lake Creek and Willow Creek subwatersheds during the winter and spring seasons. Common practices to mitigate nutrients and suspended sediments include nutrient management, no‐till, conversion of cultivated land to pasture, riparian buffers, and animal exclusion.